Descriptive analysis of medical negligence claims in septicemia patients: a review of Indian National Consumer Court judgments - Aakash A Sethi; Kalpita K. Shringarpure (MGM Journal of Medical Sciences)
Background, Aims, and Objectives: Patients admitted to intensive care units are at a higher risk of experiencing medical errors and have an increased likelihood of developing septicemia. Due to the high mortality associated with sepsis, doctors are more frequently sued for negligence. Patients alleging medical negligence in India can seek compensation through the National Consumer Dispute Redressal Commission (NCDRC). This study aims to analyze NCDRC cases where patients suffering from septicemia filed for negligence. In medical negligence cases filed by patients suffering from Septicemia, the objective is to find out the court’s outcome/verdict, the pattern of monetary compensation involved in the case, the legal standard of accepted care in the management of septicemia, and ways in which doctors can protect themselves from negligence claims, etc.